Analysis of Students’ Mathematical Critical Thinking Based on Gender in the Topic of Linear Programming - Permani, Kania Dewi; Prabawanto, Sufyani (International Conference on Elementary Education, 2020)
The critical thinking is an important skill for each students. The skill is needed in the process of solving mathematical problems. Students who have high critical thinking tend to analyze the problem situation that they met and evaluate the solution that they make either it is make sense or not. However, some reports show that the mathematical critical thinking of many vocational school students are still low and it should be increased. The research aims to analyze the students’ mathematical critical thinking based on gender factors in the topic of linear programming. The method of the research was qualitative with a descriptive approach. The subject were 2 vocational school students in Bandung, consisting of one female and one male. The research results show that, both female and male tend to meet mathematics critical thinking indicators, namely: (1) providing a simple explanation (2) checking the truth of a statement (3) observing the criteria and giving an explanation/ reason of the answers (4) making considerations and assess the answer. But when solving the problem, female student is more systematic and more careful than male student.